2003
DOI: 10.1146/annurev.cellbio.19.111401.092717
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Imprinting: Intricacies of Epigenetic Regulation in Clusters

Abstract: An intriguing characteristic of imprinted genes is that they often cluster in large chromosomal domains, raising the possibility that gene-specific and domain-specific mechanisms regulate imprinting. Several common features emerged from comparative analysis of four imprinted domains in mice and humans: (a) Certain genes appear to be imprinted by secondary events, possibly indicating a lack of gene-specific imprinting marks; (b) some genes appear to resist silencing, predicting the presence of cis-elements that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
189
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(192 citation statements)
references
References 113 publications
0
189
0
3
Order By: Relevance
“…Imprinted genes are regulated by imprinting control regions (ICRs) which are associated with blocks of tandem repeats and differential methylation (Hutter et al, 2006;Verona et al, 2003). We examined the published sequence for Sfmbt2 and found a CpG cluster near the transcriptional start site.…”
Section: Sfmbt2 Promoter Region Displays Maternal Methylation In Placmentioning
confidence: 99%
“…Imprinted genes are regulated by imprinting control regions (ICRs) which are associated with blocks of tandem repeats and differential methylation (Hutter et al, 2006;Verona et al, 2003). We examined the published sequence for Sfmbt2 and found a CpG cluster near the transcriptional start site.…”
Section: Sfmbt2 Promoter Region Displays Maternal Methylation In Placmentioning
confidence: 99%
“…Mouse studies have shown that the unmethylated maternal allele is bound by several copies of a zinc-finger protein called CTCF. (14) This creates a chromatin boundary, insulating the IGF2 gene from enhancers located downstream of H19. As a consequence, IGF2 is not expressed from the maternal allele.…”
Section: Introductionmentioning
confidence: 99%
“…This also ensures proper levels of expression at this important growthrelated domain. (14) Next to the IGF2-H19 domain lies the imprinted KCNQ1 domain (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…First, imprinted genes tend to have a clustered distribution in mammalian (15,18,19) and plant genomes (20), with the mammalian clustering appearing to be conserved in vertebrate evolution (21). Second, imprinted genes appear to modulate a limited number of types of traits, with most genes having effects on growth (especially in relation to the demand for maternal provisioning, often via the placenta) and/or behaviors (17,22), with behavioral effects being largely associated with parental and social behaviors (13,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Imprinted genes are often coregulated (19) and tend to show coordinated expression, which provides a strong opportunity for selection to favor genetic coadaptation, where combinations of beneficially interacting alleles (i.e., alleles that "work well" together) are coinherited (40). That is, given the temporal and spatial coupling of imprinted gene expression there is ample opportunity for imprinted gene products to interact in their effects on fitness, which could lead to genetic coadaptation.…”
mentioning
confidence: 99%